THE MODERATING EFFECT OF PERCEIVED SOCIAL SELF-EFFICACY, AND PERCEIVED SOCIAL SUPPORT ON THE RELATIONSHIP BETWEEN ACCULTURATIVE STRESS AND SOCIOCULTURAL ADAPTATION AMONG MYANMAR STUDENTS IN THAILAND UNIVERSITIES - Htet, Kanzar-; Mohanan, Santhosh (Scholar: Human Sciences, 2022)
The current study explored the acculturative stress of Myanmar international students studying in Thailand universities and its relation to socio-cultural adaptation moderated by personal and social factors, namely, perceived self-efficacy and perceived social support, respectively. This quantitative research utilized a descriptive type of inquiry using a self-report survey questionnaire of 120 Myanmar international students composed of 61 females and 59 males from five universities in Thailand. Findings revealed a direct negative correlation between acculturative stress and socio-cultural adaption. The students’ perceived social support can moderate this relationship. Those with low levels of perceived social support tend to have lower socio-cultural adaptation than those with high levels of perceived social support. Furthermore, perceived social self-efficacy was also found to have a moderating effect on the relationship between acculturative stress and socio-cultural adaptation. Students with low levels of perceived social self-efficacy and acculturative stress are related to lower socio-cultural adaptations. Hence, students who possess a high level of acculturative stress and with low levels of perceived social support and perceived social self-efficacy have the lowest levels of socio-cultural adaptation